Dichotomy of development aid's ambition and neoliberal imperatives: A case‐study of private‐sector development in Bangladesh. (13th June 2018) - Husain, Matt
Abstract: Development in the twenty‐first century ("neo‐liberalism") is a tool and its success and sustainability depend on how this tool is applied on a specific grounded reality. This article investigates how this modernization process continually co‐creates globalized Bangladesh through private sector development. While this field report highlights the challenges development aid donors can face in Bangladesh's post‐colonial culture, it also unveils the dichotomous traction between globalization and inequality as well as the friction poverty reduction, through private sector development, can generate in impoverished countries. Finally, this report attempts to reconsider the ways in which the aid development ambitions of equality and liberty can find a workable balance with the neo‐liberal Imperative for private sector development. This article calls for improving quality control to generate greater impact of development aid resources in developing private sectors.